The stagnation of household consumption in Japan - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2004)
In this paper, I consider the extent to which the stagnation of household consumption is responsible for the decade-long recession in Japan during the 1990s and early 2000s and the reasons for the stagnation of household consumption during this period and find that the stagnation of private investment (and inventory investment) rather than that of household consumption was the major cause of the decade-long recession, that household consumption was nonetheless relatively stagnant during this decade, and that the stagnation of household consumption was due primarily to the stagnation of household disposable income, the decline in household wealth (which in turn was due primarily to the collapse of land and equity prices), and to a lesser extent, increased uncertainty about the future (especially about old age in general and public old-age pensions in particular), the deterioration of future prospects, and deflationary expectations concerning consumer prices.
Keywords: 330; Gesamtwirtschaftlicher Konsum; Konjunktur; Japan